2017
DOI: 10.26556/jesp.v8i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Expressivism and Moore's Paradox

Abstract: No abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Woods (2014) originally operates with the idea that, on an expressivist view, "Murder is wrong" would express something like being against murder -a state that has the action-type of murdering as its object. I do the same in my earlier response to Woods (Toppinen 2014). However, the contextualist view and the ecumenical view do not say that "Murder is wrong" expresses a state of being against murder.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Woods (2014) originally operates with the idea that, on an expressivist view, "Murder is wrong" would express something like being against murder -a state that has the action-type of murdering as its object. I do the same in my earlier response to Woods (Toppinen 2014). However, the contextualist view and the ecumenical view do not say that "Murder is wrong" expresses a state of being against murder.…”
mentioning
confidence: 67%
“…In an earlier paper, I suggested that this argument can be resisted (Toppinen 2014). It is a familiar thought that a sentence such as "Murder is wrong" may, depending on the context of utterance, express, for example, a genuine moral judgment condemning murder, or a merely descriptive judgment to the effect that murder fails to meet some salient, descriptively specifiable standards (e.g., the standards that have currency in the speaker's society).…”
mentioning
confidence: 99%
“…Para un uso diferente de la paradoja de Moore contra el expresivismo cf. Woods (2014); Toppinen (2014). Para otras críticas y posibles respuestas a las mismas: véase Arena (2023, 99ss.…”
Section: Conclusiones: Discrepando Con José Juan Moresounclassified
“…For further discussion, see Beddor 2019a. 33 For other responses to Woods' challenge, see Toppinen 2014;Raskoff 2018;Franzén 2019. 34 For references, see fn.…”
Section: E N D N O T E Smentioning
confidence: 99%